From uneconomic growth to a steady-state economy - Daly, Herman E.; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2014)
'This timely collection of essays is a magnificent testament to Daly's pioneering work over four decades. Armed with clear scientific principles and an unfailing logic, Daly sets out on an urgent quest to develop an economics fit for purpose on a finite planet. The originality and clarity of thought revealed in this new collection is extraordinary. It cements Daly's status as the most visionary economist of our time.'--Tim Jackson, Centre for Environmental Strategy, University of Surrey, UK. 'Herman Daly has been leading the way on uneconomic growth and steady-state economics for nearly 50 years, and still is. His numerous contributions are increasingly relevant and influential, deeply insightful and unusually accessible to readers from all walks of life. How fortunate we are to have in a single volume so many of Daly's most important papers. Re-reading them is a pleasure and an inspiration, reading them for the first time could very well change your life.'--Peter A. Victor, York University, Canada. 'Herman Daly has helped us to realize that there is economic growth and uneconomic growth. In so doing, he reminds us that the only viable long-term option is a steady-state economy.'--Lester R. Brown, President of Earth Policy Institute and author of Full Planet, Empty Plates. 'Herman Daly is widely recognized as being the most accomplished thinker on the growth-versus-environment nexus. In this collection of essays, he discusses recent facts and arguments, fluently combining fundamental, applied and topical issues, as well as responding to green growth optimists like Paul Krugman. Acknowledging the precise and captivating style of Daly's writing, here is an excellent book for students of both economics and environmental science to start reading about environmental economics and growth. Daly gives his proposed alternative, the steady-state economy, hands and feet by elaborating a diversity of economic topics, including jobless growth, nationalizing money, regulating housing markets, facing the economic crisis and limiting free trade.'--Jeroen C.J.M. van den Bergh, University of Barcelona, Spain and Free University, Amsterdam, the Netherlands. In this important book, Herman E. Daly lays bare the weaknesses of growth economics and explains why, in contrast, a steady-state economy is both necessary and desirable. Through the course of the book, Daly develops the basic concept and theory of a steady-state economy from the 1970s limits to growth debates. In doing so, he draws on work from the classical economists, through both conflicts and agreements with neo-classical and Keynesian economists, as well as recent debates on uneconomic growth. Editorial-style policy essays substantiate Daly's argument and he provides specific application of steady-state economics to important current issues, including monetary reform, tax reform, international trade and population. The book also includes discussion and critique of ethical, as well as biophysical, presuppositions of growth. From Uneconomic Growth to a Steady-State Economy is essential reading for academics, students and researchers in the fields of ecological economics, environmental studies, economic development, resource economics and public policy.
pt. I. Early discussion of basic steady-state concepts -- pt. II. Later extensions into standard economics -- pt. III. Recent revival of the growth debate and policies for a steady state -- pt. IV. Ethical foundations of a steady-state economy -- pt. V. Short essays on current issues related to growth versus steady state.
Includes bibliographical references and index.
Description based on online resource; title from title screen (viewed November 11, 2014).
Keywords: Environmental economics; Electronic books